ANALISIS PENGARUH KUALITAS INFORMASI, KUALITAS SISTEM DAN KUALITAS PELAYANAN TERHADAP MINAT BELI ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi pada Pelanggan Traveloka di Kota Semarang) - Rinaldi, Adhitya; Santoso, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2018)
Online Travel Agent (OTA) is a new business that arises due to technological developments. The promising potential of OTA in Indonesia makes many new OTA emerged and increased in competition. Based on research conducted by W&S Digital Market Research (2014), Traveloka is in the